Arbeitsgemeinschaft: 23. bis 26. Juni 1967 - Roquette, Peter (Tagungsbericht, 1967)
I. Becker, Heidelberg; M. Becker, Tübingen; A. Brandis, Heidelberg; H. Eberle, Tübingen; G. Frey, Heidelberg; W.-D. Geyer, Heidelberg; H. Göhner, Tübingen; U. Göhner, Tübingen; P. Hahnel, Tübingen; F. Hartmann, Heidelberg; I. Heer, Heidelberg; K. Irion, Heidelberg; I. Koch, Tübingen; G. Martens, Heidelberg; R. Maulbetsch, Tübingen; E. Mendoza, Heidelberg; K. Radbruch, Tübingen; J. Ritter, Tübingen; P. Roquette, Heidelberg; W. Schmale, Tübingen; H. v. Weizsäcker, Heidelberg; M. Wolff, Tübingen; H. Zassenhaus, Columbus; H. G. Zimmer, Tübingen
Keywords: Konferenzschrift